Patient Partner Perspectives: The Experience of Participating in a Co-Designed Virtual Reality Project - Heather Thomson RN, PhD; Lisa Di Prospero MRTT, BSc, MSc; Sarah Xiao RN, PhD; Tamara Harth BA, MLIS; Laurie Legere BA, BPR; Laura Rashleigh RN, MScN; Maria Parzanese RN, MN (Journal of Patient Experience)
Patient partners (PP) are well positioned to make meaningful contributions to healthcare through their lived experiences and personal narratives. However, researchers must ensure that patients are engaged authentically and collaboratively in knowledge generation. As part of a larger project, 4 PP were engaged in the co-design of a virtual reality video aimed at promoting an understanding of patients’ lived experience with COVID-19 during the initial phase of the pandemic. This paper reports on findings from follow-up evaluation interviews with PP about their experiences participating in this project. Thematic analysis of interview transcripts resulted in 2 major themes as well as facilitators and barriers to PP engagement. Primary reasons to participate in the project were to contribute and give back to the community and make a difference for patients impacted by COVID-19. Engagement resulted in positive experiences and impacts for PP. Facilitators to engagement included feeling heard, being valued, and treated with respect. Barriers included length of time required to complete the project as well as PP health status.